Development and validation of the first consensus gene-expression signature of operational tolerance in kidney transplantation, incorporating adjustment for immunosuppressive drug therapy - Christakoudi, Sofia; Runglall, Manohursingh; Mobillo, Paula; Rebollo-Mesa, Irene; Tsui, Tjir-Li; Nova-Lamperti, Estefania; Taube, Catharine; Norris, Sonia; Kamra, Yogesh; Hilton, Rachel; Augustine, Titus; Bhandari, Sunil; et al. (EBioMedicine, 2020)
BACKGROUND: Kidney transplant recipients (KTRs) with "operational tolerance" (OT) maintain a functioning graft without immunosuppressive (IS) drugs, thus avoiding treatment complications. Nevertheless, IS drugs can influence gene-expression signatures aiming to identify OT among treated KTRs. METHODS: We compared five published signatures of OT in peripheral blood samples from 18 tolerant, 183 stable, and 34 chronic rejector KTRs, using gene-expression levels with and without adjustment for IS drugs and regularised logistic regression. FINDINGS: IS drugs explained up to 50% of the variability in gene-expression and 20-30% of the variability in the probability of OT predicted by signatures without drug adjustment. We present a parsimonious consensus gene-set to identify OT, derived from joint analysis of IS-drug-adjusted expression of five published signature gene-sets. This signature, including CD40, CTLA4, HSD11B1, IGKV4-1, MZB1, NR3C2, and RAB40C genes, showed an area under the curve 0⋅92 (95% confidence interval 0⋅88-0⋅94) in cross-validation and 0⋅97 (0⋅93-1⋅00) in six months follow-up samples. INTERPRETATION: We advocate including adjustment for IS drug therapy in the development stage of gene-expression signatures of OT to reduce the risk of capturing features of treatment, which could be lost following IS drug minimisation or withdrawal. Our signature, however, would require further validation in an independent dataset and a biomarker-led trial. FUNDING: FP7-HEALTH-2012-INNOVATION-1 [305147:BIO-DrIM] (SC,IR-M,PM,DSt); MRC [G0801537/ID:88245] (MPH-F); MRC [MR/J006742/1] (IR-M); Guy's&StThomas' Charity [R080530]&[R090782]; CONICYT-Bicentennial-Becas-Chile (EN-L); EU:FP7/2007-2013 [HEALTH-F5-2010-260687: The ONE Study] (MPH-F); Czech Ministry of Health [NV19-06-00031] (OV); NIHR-BRC Guy's&StThomas' NHS Foundation Trust and KCL (SC); UK Clinical Research Networks [portfolio:7521].
Keywords: logistické modely; Consensus; Humans; Case-Control Studies; lidé středního věku; transplantační tolerance; studie případů a kontrol; Operational Tolerance; genové regulační sítě; Graft Rejection; Female; Aged; Immunosuppressive Drugs; dospělí; Kidney; Gene Regulatory Networks; senioři; lidé; Biomarkers; imunosupresiva; konsensus; Adult; Immunosuppressive Agents; transplantace ledvin; ženské pohlaví; Male; Middle Aged; stanovení celkové genové exprese; Transplantation Tolerance; Kidney Transplantation; Real-Time Polymerase Chain Reaction; RT-qPCR; Transplantation; Gene Expression Profiling; mužské pohlaví; Logistic Models; kvantitativní polymerázová řetězová reakce; rejekce štěpu